Review of evidence on handling hazardous drugs and Products in Urology Services; consensus document between the Spanish Urology Association and the Spanish Society of Health-System Pharmacists - Miguel Unda-Urzáiz (Farmacia Hospitalaria, 2018)
Objective: The intravesical administration of hazardous drug products is a standard practice in the urology setting, which potentially exposing medical personnel to these drug products. It was deemed necessary to have a consensus document among the scientific societies involved (the Spanish Urological Association and the Spanish Society of Hospital Pharmacy) that collects the best available evidence on the safest handling possible of dangerous drug products in the setting of urology departments. Method: We reviewed the legislation and recommendations on the handling of dangerous drug products, both at the national and international level. Results: There is national legislation and regulations for protecting workers who handle dangerous drugs and products, as well as recommendations for handling to protect both the product and workers. Discussion: Following the strategic lines of the European Parliament for 2014- 2020 in the chapter on occupational safety and health, the Spanish Urological Association and the Spanish Society of Hospital Pharmacy proposed a series of actions that decrease the risks of exposure for practitioners and caregivers involved in the handling of these products. Conclusions: After this review, 19 recommendations were established for handling dangerous drug products, which can be summarised as the need to train all individuals involved (from management teams to patients and caregivers), adopt systems that prevent contaminating leaks, implement exposure surveillance programmes and optimise available resources.